2022
DOI: 10.24136/eq.2022.033
|View full text |Cite
|
Sign up to set email alerts
|

Actual rate of the management fee in mutual funds of different styles

Abstract: Research background: Exponential growth of passive mutual funds after 2007?2008 global financial crisis put pressure on active fund managers to lower the management fees. The real costs of active fund management are, however, very often higher than the values of management fees reported publicly. Thus it is not easy to decide on the quality of the fund management and estimate the level of management charges optimal for the future fund performance. Purpose of the article:  In this study, we propose to utilize a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…2 into the influence of other factors on the relationship between market risk and mutual fund performance. Perez and Szymczyk (2022) revealed that the impact of market risk on mutual fund performance is moderated by factors such as fund size and investment style. Given the debates, this research proposes a significant association between mutual fund performance and the market risk factor.…”
Section: Business Management and Strategymentioning
confidence: 99%
“…2 into the influence of other factors on the relationship between market risk and mutual fund performance. Perez and Szymczyk (2022) revealed that the impact of market risk on mutual fund performance is moderated by factors such as fund size and investment style. Given the debates, this research proposes a significant association between mutual fund performance and the market risk factor.…”
Section: Business Management and Strategymentioning
confidence: 99%
“…However, it is worth to repeat such study in emerging markets like the Polish one, since it is very dynamically growing in the European Union, but also because it has a different history, background, and the structure of the investment funds than in the most developed fund market in the world, namely in the USA. In Poland, the research has been carried out occasionally so far (Miziołek, 2015;Bogdanowicz et al, 2017;Trzebiński, 2022), and has been limited mainly to equity funds (except Perez and Szymczyk [2022] who studied different types of funds).…”
Section: Introductionmentioning
confidence: 99%